O009 Differential attainment at the Intercollegiate Membership of the Royal Colleges of Surgeons (MRCS) examination according to gender, ethnicity, age and socioeconomic factors. (22nd July 2022) - Ellis, R; Brennan, PA; Lee, AJ; Scrimgeour, DSG; Cleland, J
Abstract: Introduction: The lack of diversity at senior and leadership positions in surgery highlights concerns that some groups of individuals face barriers to progression in surgical training. This study aimed to investigate whether there is group-level differential attainment (DA) at MRCS, a mandatory postgraduate examination for UK surgical trainees. Methods: All UK graduates attempting MRCS Part A ( n =5, 780) and Part B ( n =2, 600) between 2013–2019 were identified using the UK Medical Education Database. Univariate associations with MRCS performance were identified using chi-squared tests. Multiple logistic regression identified independent predictors of first-attempt MRCS success, adjusted for medical school performance. Results: We found statistically significant differences in MRCS pass rates according to gender, ethnicity, graduate status, childhood socioeconomic status and educational background (all P<0.05). After adjusting for prior academic attainment, being a non-graduate (odds ratio [OR] 1.98, 95%CI 1.44–2.74) or male (OR 2.34, 95%CI 1.87–2.92) were independent predictors of MRCS Part A success. Being a non-graduate (OR 1.77, 95%CI 1.15–2.71) or having attended a fee-paying school (OR 1.51, 95%CI 1.08–2.10) were independent predictors of MRCS Part B success. Black candidates were significantly less likely to pass MRCS Part B at their first attempt (OR 0.41, 95%CI 0.18–0.92) as were Asian candidates (OR 0.49, 95%CI 0.35–0.69 for) in comparison to White candidates. Conclusion: We found significant DA at MRCS that cannot be attributed to learner deficit. Royal Colleges and training institutions now need to identify and address the causes of these attainment differences to facilitate equitable career progression for surgical trainees. Take-home message: We found significant DA at MRCS that cannot be attributed to learner deficit. Royal Colleges and training institutions now need to identify and address the causes of these attainment differences to facilitate equitable career progression for surgical trainees.